Outcome of desmopressin therapy on nocturnal enuresis in 6-15 years age group children of selected schools in Dhaka City - Afrin, Tanjila; Billah, M. Masum; Hossain, M. Iqbal; Fardous, Jannatul; Khan, M. Anwar Hossain; Alam, M. Kabir; Jesmin, Habiba; Ashraf, Rezwana (International Journal of Contemporary Pediatrics, 2026)
Background: Nocturnal enuresis (bedwetting) is a common pediatric condition affecting children’s physical, emotional, and social well-being. Desmopressin, a synthetic antidiuretic hormone analogue, is widely used to reduce nocturnal urine production. However, evidence on its effectiveness in school-aged children in Dhaka City remains limited. To evaluate the outcomes of Desmopressin therapy combined with behavioral interventions compared to behavioral therapy alone in children aged 6-15 years with primary monosymptomatic nocturnal enuresis. Methods: A quasi-experimental study was conducted in two selected schools and the Department of Pediatric Nephrology, NIKDU, Dhaka, from February 2022 to July 2023. A total of 104 children meeting inclusion criteria were enrolled and divided into two groups: Group A (Desmopressin + behavioral therapy, n=52) and Group B (behavioral therapy only, n=52). Baseline assessment included demographics, sleep fragmentation, number of wet nights, laboratory investigations, and ultrasonography of the KUB region. Follow-up was performed at 2 weeks, 12 weeks, and 3 months post-treatment to assess reduction in wet nights, initial success, relapse, and adverse effects. Data were analyzed using SPSS v22; p<0.05 was considered significant. Results: Demographics and baseline characteristics were comparable between groups. Both groups demonstrated a decrease in wet nights per week; however, Group A showed significantly greater improvement at week 12 (2.26±1.17 vs. 2.82±1.15, p=0.002) and at the end of the study (1.79±1.18 vs. 2.61±1.06, p<0.001). Initial treatment success was similar (52.1% vs. 47.1%, p=0.698), while relapse rates were higher in Group A (68.0% vs. 31.0%, p=0.070), although not statistically significant. Only mild adverse effects were observed in Group A (headache 6.4%, nausea 4.3%, vomiting 4.3%); no adverse effects were reported in Group B. Laboratory and ultrasonographic parameters remained normal in both groups. Conclusion: Desmopressin combined with behavioral therapy provides faster and more pronounced reduction in wet nights compared to behavioral therapy alone, while both interventions are safe and well tolerated. These findings support combined therapy for rapid symptom control and behavioral therapy as a reliable long-term management strategy for pediatric nocturnal enuresis.